1996
DOI: 10.1111/j.1939-1676.1996.tb02032.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Whole Blood Glutaraldehyde Coagulation Test for the Detection of Failure of Passive Transfer in Calves

Abstract: The accuracy of a commercially available whole blood glutaraldehyde clot test in the detection of failure of passive transfer (serum immunoglobulin [IglG, <1,000 mg/dL) in neonatal calves was evaluated. Serum samples were obtained from 242 calves ranging in age from 1 to 8 days, and comparisons were made with serum lgG, concentrations determined by radial immunodiffusion. Both the sensitivity and specificity of the currently marketed whole blood glutaraldehyde clot test are inadequate for routine diagnostic us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Recently, several articles have been published that have fine-tuned these various testing methods to provide more accurate values for defining immunoglobulin levels in the neonate. 25,47,65,66 Although the identification of optimum threshold values for these tests is useful, they must be kept in perspective and their use not overinterpreted, Various studies that have examined the relationship between serum immunoglobulin levels in calves and disease incidence and subsequent production have had conflicting results. Several studies have demonstrated significant increases in morbidity and mortality in calves suffering failure of passive transfer and have been reviewed.…”
Section: Concept Of Failure Of Passive Transfermentioning
confidence: 99%
“…Recently, several articles have been published that have fine-tuned these various testing methods to provide more accurate values for defining immunoglobulin levels in the neonate. 25,47,65,66 Although the identification of optimum threshold values for these tests is useful, they must be kept in perspective and their use not overinterpreted, Various studies that have examined the relationship between serum immunoglobulin levels in calves and disease incidence and subsequent production have had conflicting results. Several studies have demonstrated significant increases in morbidity and mortality in calves suffering failure of passive transfer and have been reviewed.…”
Section: Concept Of Failure Of Passive Transfermentioning
confidence: 99%
“…Imprecision in RID assay replicates from the same sample have been noted and are attributed preliminary validation of a calf-side test for diagnosis of failure of transfer of passive immunity in dairy calves I. elsohaby * † 1 and G. p. Keefe * 4755 to inconsistencies in the assay standards (Ameri and Wilkerson, 2008). Other than RID, serum total protein determination using refractometry, sodium sulfite turbidity test, zinc sulfate turbidity test, ELISA, serum γ-glutamyl transferase activity, and whole-blood glutaraldehyde coagulation test have been described with varying degrees of accuracy for predicting IgG concentrations in calves (Tyler et al, 1996a;Parish et al, 1997;Weaver et al, 2000). The turbidimetric immunoassay described by Etzel et al (1997) performed well in calves (Dawes et al, 2002;Alley et al, 2012) and foals (Davis et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Several assays are available to assess passive immunoglobulin transfer status in newborn calves (Tyler et al, 1996a;Parish et al, 1997;Weaver et al, 2000). The radial immunodiffusion (RID) assay is the reference standard method for determining passive immunoglobulin transfer by measuring the quantity of IgG in the serum (Weaver et al, 2000;Godden, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been reported to evaluate passive transfer status in neonatal calves including zinc sulfate and sodium sulfite turbidity tests [10,11], glutaraldehyde coagulation tests [12], measurement of serum gamma-glutamyl transferase (GGT) activity [13,14], and direct measurement of IgG through single radial immune diffusion (SRID), which is considered the gold standard [11,13,15]. Serum total protein (TP serum ) concentration has been shown to correlate with serum IgG concentration [10,16].…”
Section: Introductionmentioning
confidence: 99%